Do Contact and Empathy Mitigate Bias Against Gay and Lesbian People Among Heterosexual First-Year Medical Students? A Report From the Medical Student CHANGE Study. (May 2015) - Burke, Sara E.; Dovidio, John F.; Przedworski, Julia M.; Hardeman, Rachel R.; Perry, Sylvia P.; Phelan, Sean M.; Nelson, David B.; Burgess, Diana J.; Yeazel, Mark W.; van Ryn, Michelle
<x xml:space="preserve">Abstract</x> Purpose A recent Institute of Medicine report concluded that lesbian and gay individuals face discrimination from health care providers and called for research on provider attitudes. Medical school is a critical juncture for improving future providers' treatment of sexual minorities. This study examined both explicit bias and implicit bias against lesbian women and gay men among first-year medical students, focusing on two predictors of such bias, contact and empathy. Method This study included the 4, 441 heterosexual first-year medical students who participated in the baseline survey of the Medical Student Cognitive Habits and Growth Evaluation Study, which employed a stratified random sample of 49 U.S. medical schools in fall 2010. The researchers measured explicit attitudes toward gay and lesbian people using feeling thermometer self-assessments, implicit attitudes using the Implicit Association Test, amount and favorability of contact using self-report items, and empathy using subscales of the Interpersonal Reactivity Index. Results Nearly half (45.79%; 956/2, 088) of respondents with complete data on both bias measures expressed at least some explicit bias, and most (81.51%; 1, 702/2, 088) exhibited at least some implicit bias against gay and lesbian individuals. Both amount and favorability of contact predicted positive implicit and explicit attitudes. Both cognitive and emotional empathy predicted positive explicit attitudes, but not implicit attitudes. Conclusions The prevalence of negative attitudes presents an important challenge for medical education, highlighting the need for more research on possible causes of bias. Findings on contact and empathy point to possible curriculum-based interventions aimed at ensuring high-quality care for sexual minorities.